Metodologia para análise de imagens de baixa resolução, para definição de MUB (Mapa Urbano Básico) para apoio às concessionárias de distribuição - Santos, Paulo Victor dos (2018)
The high cost of geo-referenced technologies capable of keeping up-to-date geographic information system data from a power distribution company, which has the basic urban map as the primary data layer, may result in non-purchase of this product, making information outdated or incomplete, generating in addition to losses, rework and confusion when there is a need to do verifications and validations that could be performed remotely. This proposal to support energy distribution concessionaires will use Computational Vision (VC) and Digital Image Processing (PDI) methods, allowing a low cost and efficient maintenance in layers of buildings present in basic urban maps of distributors. This findings might result in possible savings, without any need of displacement in the field to observe a situation that can be evidenced remotely.